The Algebra of differential operators for a matrix weight: An ultraspherical example - Zurrián, Ignacio Nahuel (2017)
In this article we study in detail algebraic properties of the algebra D(W) of differential operators associated to a matrix weight of Gegenbauer type. We prove that two secondorder operators generate the algebra, indeed D(W) is isomorphic to the free algebra generated by two elements subject to certain relations. Also, the center is isomorphic to the affine algebra of a singular rational curve. The algebra D(W) is a finitely generated torsion-free module over its center, but it is not flat and therefore it is not projective. This is the second detailed study of an algebra D(W) and the first one coming from spherical functions and group representations. We prove that the algebras for different Gegenbauer weights and the algebras studied previously, related to Hermite weights, are isomorphic to each other. We give some general results that allow us to regard the algebra D(W) as the centralizer of its center in the Weyl algebra. We do believe that this should hold for any irreducible weight and the case considered in this article represents a good step in this direction.